KONDISI SOSIAL EKONOMI ANGGOTA KELOMPOK WANITA TANI DALAM PEMANFAATAN TANAH PEKARANGAN DI KABUPATEN NGANJUK - Sudarmini Sudarmini; Sumarji Sumarji; Ratna Dewi Mulyaningtiyas (SINTA Journal (Science, Technology, and Agricultural), 2023)
ABSTRACTEmpowerment is one of the solutions to overcome social problems that hit, including poverty. Utilization of Yard Land is one way to empower members of the Women Farmer Group (KWT). The purpose of this study was to determine the socio-economic conditions of the members of the Women Farmer Group in the Utilization of Yard Land in Nganjuk Regency. This type of research uses qualitative methods. This research be carried out in Prambon, Tanjunganom and Ngronggot Districts, Nganjuk Regency. This research will be carried out for 2 (two) months, from November to December 2022. The data collected consists of primary data and secondary data. Primary data is planned to be obtained by several methods, including direct interviews, observation methods or structured observations from Women Farmer Groups (KWT). The method of determining informants was purposive sampling, namely 15 people, 5 people were taken from each sub-district. Data analysis using qualitative analysis. The results of the study were that the condition of socio-economic factors was related to the role of farmer members of women's farmer groups in the use of yard land. with a group of women farmers, they can develop their ability to create creative ideas and increase their household income/economy by utilizing the yard around the house. Socio-economic factors gender, age, education, number of family dependents, experience.Keywords: Farming Women's Group, Socio-Economic Conditions, Utilization of Yard Land